Registro de libélulas (Odonata) predadas por aranhas (Araneae) na Mata Atlântica, no Sul do Brasil - Gouvêa, Taiguara P.; Almeida , José A. M.; Shimamoto, Carolina Y.; Barbado, Norma; Souza, Marcos M. (Entomological Communications, 2023)
Dragonflies are insects that act as predators and prey, both in freshwater and associated terrestrial ecosystems, which makes the understanding of trophic relationships established by these insects important. In this sense, the present study aimed to report the predation of Odonata by Araneae in areas of seasonal semideciduous forest, phytophysiognomy of the Atlantic Forest at the Iguaçu National Park (PARNA Iguaçu), and in the Bela Vista Biological Refuge (RBBV). The records occurred at random in 2021 from December 13 to 21, and in 2022 from January 4 to April 22. Five individuals of three species and two morphospecies of Odonata preyed upon by three morphospecies of spiders were recorded. Predation of Odonata by spiders seems to be frequent in different ecosystems, but further studies are required to understand the impact of this predation on the size of dragonfly communities in the Brazilian Atlantic Forest biome.